(untitled) (Journal of Economic Research & Business Administration, 2015)
The article deals with the banking channel of transmission mechanism of monetary policy in the economies of Central and Eastern Europe and Kazakhstan. A review of the banking sector of Kazakhstan is given. Gerfindal coefficient is calculated, which reveals a high degree of concentration in the sector.